Aggression, violence and resilience in offender healthcare services - Hodgkinson, Sarah (2020)
Service user to staff violence is well documented in healthcare service literature. However, there appears to be little consensus on the definition of this type of violence. This in turn limits ways of measuring different types of service-user aggression as experienced by staff. Nevertheless, healthcare workers in general are particularly at risk of experiencing workplace violence. Previous research would indicate that staff working in forensic-based services, although still experience aggression and violence, may have mechanisms in place that serve a protective function. Further investigation of such phenomena as resilience is warranted.